(3GdYed HGdcQI GdadcjIs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3PcQJ (B_ (3CYRc Gddg (B_ (3Cf GdcQI GdadcjI hGdYed HgG heG QCjJ ef XghQ GNJdGa eWGdY GdTeS heZGQHgG ajgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIChdgG eNJda bdjdkG Yf GdfSNI CMeO GdKGdK HQbe (B3505 5 (3hJJab ai BNQgG eY BNQ fSNI CMeO GdKGdK HGNJdGa ai HYV GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B222 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B365 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs